Vancomycin-resistant enterococci infection and predisposing factors for infection and mortality in patients with acute leukaemia and febrile neutropenia. (December 2020) - Kirkizlar, Tugcan Alp; Akalin, Halis; Kirkizlar, Onur; Ozkalemkas, Fahir; Ozkocaman, Vildan; Kazak, Esra; Ozakin, Cuneyt; Bulbul, Esra Nur; Ozboz, Ezgi Sezen; Ali, Rıdvan
Highlights: Vancomycin-resistant enterococcus infections increase morbidity and mortality especially in neutropenic patients. Pay attention for VRE infection in VRE colonized patients who are coinfected and have >15 days of colonization. Invasive procedures should be postpone if possible in VRE colonized patients. Be aware in terms of increased mortality in patients who are older, female, neutropenic and coinfected. Abstract: Background: Vancomycin-resistant enterococcus (VRE) is an infectious agent that can increase morbidity and mortality, especially in patients with neutropenia in haematology departments. We analysed VRE infections and mortality rates among VRE colonized patients with acute leukaemia, defined predisposing risk factors for infection and mortality, and investigated the influence of daptomycin or linezolid treatment on mortality. Patients-Methods: We included 200 VRE colonized adult acute leukaemia patients with febrile neutropenia between January 2010 and January 2016. Data were collected from electronic files. Results: There were 179 patients in the colonized group, and 21 patients in the infected group. Enterococcus faecium (van A) was isolated from all patients. The infection rate was 10.5 %, and the types of infections noted were as follows: bloodstream (n = 14; 66.7 %), skin and soft tissue (n = 3; 14.3 %), urinary (n = 2; 9.5 %), and others (9.5 %). In the multivariate logistic regression analysis, exposure to invasive procedures, coinfection status, and >15 days of VRE positivity were independent risk factors for VRE infections. In hospital mortality rates were 57.1 % in the infected group, and 9.5 % in the colonized group (p < 0.001). Older age, female gender, absolute neutropenia, and coinfection status were statistically significant predictor of survival. Conclusion: Vancomycin-resistant enterococcus infections are associated with high morbidity and mortality in haematology patients with neutropenia. Clinicians should be aware of predisposing risk factors for VRE infection to avoid unfavourable outcomes. We believe that larger studies are necessary regarding the influence of treatment with daptomycin and linezolid.